Peran Fear of Missing Out Terhadap Phubbing pada Siswa SMA Kristen di Kota Surakarta - Ardha Strinaricwari; Sujoko Sujoko; Yustinus Joko Dwi Nugroho (Universitas Muhammadiyah Jember, 2023)
Technological developments make it easy for Generation Z, namely high school students, to fulfill their social needs, to actualize themselves, and to connect with many individuals both around them and far away. This then becomes a need that continues to be sought and must be met which triggers the indication of Fear of Missing Out. The fulfillment of these social needs is then found through social media on their gadgets. From here, Phubbing's behavior arises because they are busy looking for information and want to connect with their friends in cyberspace.This study aims to determine the relationship between Fear of Missing Out on Phubbing in Christian high school students in the city of Surakarta. The hypothesis proposed in this study is